(3fhGOQ GdCKQ aj Ydj Ydjg GdSdGe NjQ GdHTQs - (3GdEjdGaj Gdbej, CHh eMeO, GHf GdQGRj, LYaQ Hf CMeO Hf Ydj, J b (B5 (3g`s ((3GdfLa GdCTQas)
(3ChdgG (B:s
(3GdMeO ddg (B...(3MOKfG CHh eMeO LYaQHf ehSi GdJdYcHQj bGd LOKfj CMeO Hf eMeO Hf SYjO bGd MOKfj eMeO Hf YHjOI Hf YJHI GdcfOj bGd MOKfj YHO GdQMef Hf ShjO Yf CHjg Yf GdCYeT (B...s
(3BNQgG (B:s
... (3aSeYJg jbhd (B: (3CeG JQVi Gf Jchf GfJ CNj aj GdOfjG hGdBNQI hGfJ NjQ CeJj aj GdOfjG hGdBNQI (B. (3Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1\486s
(3GdPQjYI (B24 - 208 (1837 )s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds